The Nature of Conditional Sentences in Nyakyusa (Journal of Humanities & Social Science (JHSS), 2022)
The mechanisms utilized to introduce conditional construction in Nyakyusa are partlysimilar to the patterns available in some Bantu languages because its protasis isintroduced by the word l??nga. The counterfactual marker angali introduces theapodosis of the counterfactual sentences, similar to Zulu and Swahili. The maindifference is that Nyakyusa differentiates reality and unreality situations primarilythrough TAM formatives. For instance, realistic situations manifest in future and presenttenses while unrealistic events are primarily indicated by remoteness in past tense.